Shocks and stability of risk preferences - Stein Terje Holden; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2021)
While economists in the past tended to assume that individual preferences, including risk preferences, are stable over time, a recent literature has developed that indicates that risk preferences respond to shocks. This paper combines survey data and field experiments with three different tools that facilitated elicitation of dis-aggregated measures of risk preferences, including utility curvature, probability weighting and loss aversion. By treating the recent shocks as natural experiments, the study assessed the sensitivity of each of these risk preference measures to the recent idiosyncratic and covariate (drought) shocks among a sample of resource-poor young adults living in a semi-arid rural environment in Sub-Saharan Africa. The results show that the dis-aggregated risk preference measures revealed substantial shock effects that were undetected when relying on a tool that elicited only one single measure of risk tolerance. Both the timing and covariate nature of the shocks affected the dis-aggregated measures of risk preferences differently, pointing towards the need for further studies of this kind in different contexts.
Keywords: C93; D81; 330; Covariate shocks; Idiosyncratic shocks; Stability of riskpreference parameters; Field experiment; Ethiopia